Entre a política e a religião: o golpe civil-militar de 1964 na cidade de Esplanada, Bahia - Lima, Thiago Machado de (2015)
On March 31, 1964 the outbreak of a civil-military coup overthrew President João Goulart Republic (PBT). In this process, a series of repressive actions, led by the Brazilian armed forces articulated with civilians, has been unleashed throughout the country. The city of Esplanada, located on the north coast of Bahia, suffered directly with mishaps generated by this coup d'etat. A week after the deposition of the President, the town was invaded by dozens of soldiers of the 6th Military Region (Bahia-Sergipe) that disfigured the local political scene. The Mayor, Erikson Orlando Carvalho Lins (PSP), popularly known as Dr. Neno, was deposed, arrested and responded to a Military Police Inquiry (IPM) on charges of being element "subversive" and have attack on the "National Security "but even through all this, the political still found ways to react and challenge of their opponents in the Civil Justice. Given these facts, we have developed this thesis an analysis of the impact of Civil-Military Coup of 1964 in the city of Esplanada focusing on the repressive situation experienced by the Mayor Dr. Neno. We seek to understand the factors that led the military to have the esplanadense political target, the development that had every stage of their repression, subjects, political groups and institutions, such as the Catholic Church, which have been directly and indirectly involved in this process, participation of the local population, the mechanisms used by the Mayor to undertake a reaction, and the outcome of this story. The time frame established for the work had as goal the year 1962 (last general election held in Bahia before the deposition of President Joao Goulart) and 1964 (when the coup).